Furosemide Increases GABAA Receptor Activity via Antagonism to Sodium-Potassium-Chloride Cotransporter 1 In Silico and In Vivo - Siregar, Marsintauli Hasudungan; Nurdiana, Nurdiana; Bal’afif, Farhad; Djajalaksana, Susanthy; Setiawansyah, Arif (Pandawa Institute, 2026)
GABAA receptor dysfunction and altered chloride homeostasis significantly contribute to seizure pathophysiology, with the sodium-potassium-chloride cotransporter 1 (NKCC1) playing a crucial role in regulating neuronal excitability. This study investigated furosemide's capacity to enhance GABAA receptor activity through NKCC1 antagonism and evaluated its therapeutic profile in combination with diazepam for seizure management. Comprehensive molecular docking analyses were conducted to assess binding affinities of furosemide and diazepam to NKCC1, followed by in vivo experiments using pentylenetetrazol-induced seizure models to evaluate GABAA receptor expression, seizure duration, and multiple pathophysiological biomarkers. Molecular analysis revealed that furosemide demonstrated measurable NKCC1 binding capacity (binding energy: -7.09 kcal/mol; Ki: 6.34 µM), though significantly lower affinity compared to diazepam (binding energy: -7.83 kcal/mol; Ki: 1.81 µM). The furosemide-diazepam combination exhibited complex competitive binding interactions, with furosemide substantially reducing diazepam's NKCC1 binding affinity. NKCC1 antagonism by furosemide effectively enhanced GABAA receptor expression by 29.8 ± 1.60% when used alone and 37.60 ± 2.0% in combination with diazepam. However, combination therapies resulted in significantly longer seizure durations (80 ± 3.0 s) compared to diazepam monotherapy (42.5 ± 2.10 s), suggesting antagonistic interactions on acute seizure suppression that may reflect altered chloride gradients or competitive pharmacokinetic effects. Despite reduced efficacy in seizure termination, combination therapy demonstrated selective advantages in other pathophysiological domains, including superior blood-brain barrier protection (reduced albumin level to 90.90 ± 2.70 µg/mL) and reduced excitotoxic damage. These findings indicate that furosemide-diazepam combination therapy presents a complex therapeutic profile characterized by trade-offs between acute seizure control and neuroprotective mechanisms. The data suggest potential utility in maintenance therapy or prevention of seizure-related complications rather than acute seizure termination, warranting further investigation into temporal optimization strategies and dose modifications.